Oxidation of a P-C Bond under Mild Conditions - Ilić, Gordana (2016)
The reactivity of phosphenium dication [(Ph3P)2C-P-NiPr2]2+, 12+, towards pyridine N-oxide (O-py) has been investigated. The resulting oxophosphonium dication [(Ph3P)2C(NiPr2)P(O)(O-py)]2+, 22+, was surprisingly stabilized by a less nucleophilic O-py ligand instead of pyridine (py). This compound was then identified as an analogue of the elusive Criegee intermediate as it underwent oxygen insertion into the P[BOND]C bond through a mechanism usually observed for Baeyer–Villiger oxidations. This oxygen insertion appears to be the first example of a Baeyer–Villiger oxidation involving O-py.